Nationality matters: The geographic origin of multinationals and the productivity of their foreign affiliates - Christian Arndt; Julia Spies (Institut für Angewandte Wirtschaftsforschung (IAW), 2012)
While quantifying the foreign ownership premium has received a lot of attention in the empirical literature, there is only little known about productivity variations between foreign affiliates of multinational firms. In order to enhance the understanding of the economic causes of this heterogeneity we analyze the impact of various institutional and economic characteristics of the countries in which the multinational parent companies are located on the productivity of their affiliates. Using a full record of the population of foreignowned affiliates in Germany we find that affiliates' mean performances differ markedly when grouped by the country of their parent firm. We show that gravitational forces and institutional characteristics of the country of the parent, such as the availability of credit and the freedom to trade internationally, co-determine the foreign-owned affiliates' performances in a significant way. Moreover, the intensity of the impact depends on the intensity of the ownership link between the parent and its affiliate. Some residual impact of nationality remains.
Keywords: F2; O2; O1; 330; Foreign direct investment; productivity spillover; investor country characteristics; Auslandsniederlassung; Direktinvestition; Ausländisch; Produktivität; Multinationales Unternehmen; Schätzung; Deutschland; Standortfaktor; Welt